Oral health status among secondary school students in Mosul City Centre/Iraq - Aisha A Qasim (University of Mosul, College of Dentistry, 2007)
Aims: To evaluate the oral hygiene and gingival health among secondary school students and to find if there was any variation between age and sex groups in Mosul City Centre. Material and Methods: A sample of 630 students aged 16-18 years old (278 males, 352 females) were examined using plaque index score and gingival index. The clinical examinations were carried out in the school using plane mouth mirrors, WHO periodontal probes to detect the dental plaque and gingival health. Results: Showed that the mean plaque score for the total sample was 0.96, the plaque index increased with age. Females reported less mean plaque scores than males with statistically significant difference between them. The mean gingival score was 0.56 for the total sample and it increased with age. There was a significant difference between males and females. The study revealed that 35.9% of the total sample did not brush their teeth. Therefore the objective of dental health education to those subjects is to brush their teeth regularly and to improve the effectiveness of oral hygiene practice. Conclusion: Periodontal disease is indirectly related to the exposure of bacterial plaque for long time which calls for coordinated planning of preventive strategies and urgent priorities